Automated ultrasonic inspection of heat exchanger tubesheets welds - Reynard, Iain Michael (Department of Mechanical Engineering, 2024)
The objective of this research was to design an automated scanning and signal interpretation system for ensuring the integrity of the welds in a specific heat exchanger presently used in industry. The First Effect Steam Chest is a shell and tube, one pass type of heat exchanger used in the production of chlorine. A caustic soda/salt mixture is pumped through the bottom channel head through the tubes whilst steam passes through the shell. There are nine hundred and eighty tubes in the tube bundle, welded to the outer surface of the tubesheet. One such heat exchanger, approximately four years after installation, revealed severe erosion of the steam chest's tubing by the caustic soda, allowing leakage of the steam. With the high• cost of replacement, maintenance tasks were performed to prolong the life of the heat exchanger. These included improving the design of tube welds and checking the integrity of these welds before commissioning. Inspection methods available for the inspection of the welds were limite9 to manual techniques. This proved to be very labour intensive, leading to operator fatigue. Furthermore, the interpretation of the results from the inspection equipment was subjective. Lastly, no record of the inspection data was kept for future comparisons. It was thought that these problems could be overcome by an automated scanning and signal interpretation system. A survey of the automated scanning equipment commercially available revealed that most scanning systems were designed for eddie current inspection. Furthermore, most equipment was found to either be designed for a specific heat exchanger configuration, and thus was not suitable for the abovementioned application, or was designed with the nuclear industry in mind, thus being unnecessary complicated and consequently overpriced. Thus, it was concluded that a dedicated scanning system would have to be designed for the application.